High-Growth Firms and the Labor Market Entry of First-Generation Immigrants - Daunfeldt, Sven-Olov; Seerar Westerberg, Hans (Senate Hall, 2020)
The number of refugees in Europe has increased dramatically in recent years, and many countries are facing great challenges to integrating these refugees into their societies. A small group of high-growth firms have at the same time attracted attention because they create the most jobs at any given point in time. Using matched employer-employee data from Statistics Sweden, we find that these high-growth firms in general are more likely to recruit first-generation immigrants that are unemployed. This provides support for the hypothesis that managers in high-growth firms, to greater extents, recruit marginalized individuals because they want to take advantage of their growth opportunities. Rapidly growing firms are thus less selective in their hiring decisions, and policies that are focused on increasing the number of high-growth firms might also help immigrants who face difficulties entering the labor market.
Keywords: firm growth|gazelles|high-growth firms|immigration|integration